Peningkatan Aktivitas Dan Hasil Belajar Ipa Melalui Model Picture And Picture Di Kelas IV SD Inpres Watujara - Nining Sariyyah (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The purpose of this research is to increase the activities and learning outcomes of science subject by applying the Picture and Picture model. The research was carried out in the Class Action Research (CAR) stage of the Kemmis and Mc Taggart design which included the planning stage (Plan), the implementation stage (Act), the observation stage and the reflection stage. The data taken are activity data and student learning outcomes. Data was collected using observation techniques, field notes, tests and interviews. Data were analyzed by qualitative descriptive technique. The results of research that have been carried out in two cycles show an increase in science learning activities and outcomes after the Picture and Picture model is applied.